USING COMPUTER MATHEMATICS SYSTEMS IN A HIGH SCHOOL COURSE - Kydyrbayeva, А.; Mukanova, Ж.; Akishev, Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2022)
Currently, much attention is paid to computer technologies in the field of education. Teachers should apply not only classical forms of teaching, but also master new ways of studying disciplines using computers and computer technologies. Among computer technologies that allow solving many problems of an applied nature, computer mathematics systems are of particular interest. We decided to study the question, are these systems applicable when studying mathematics in a high school course? Studying various sources of information in the course of our research, we came to the conclusion that this issue is very controversial. We conducted our research in the form of an experiment with math teachers who passed a training workshop on the basics of working with the MathCad package. At the end of the seminar, the teachers conducted experimental lessons in their classrooms and gave an objective conclusion on the use of the MathCad package in teaching mathematics. The use of computer mathematics systems meets the basic didactic principles well. And, therefore, they can be used in a high school course.